A Youth Participatory Project to Address STIs and HIV among Homeless Youth. Issue 3 (3rd July 2019) - Dang, Michelle T.; Amos, Aaron; Dangerfield, Monique; Ford, Brian; Kern, Kayla; Moon, Martha
ABSTRACT: The purpose of this study was to conduct a youth participatory action research project to address the disparities in sexually transmitted infection (STI) and HIV rates among homeless youth. Four youth served as co-investigators and cultural informants for the project. The team conducted focus groups ( N = 22; ages 16–22) and in-depth interviews ( N = 20; ages 18–24) with homeless youth to explore decisions about condomless sex, knowledge of STIs and HIV, health-care access for STI-related services, and perceptions about STI testing. Findings revealed that homeless youth have good general knowledge about STIs, are receptive to STI testing for themselves and their sexual partners, and have heightened concerns about being HIV positive and peers knowing their STI status. Results from the current study could contribute to the development of youth-informed tailored interventions to increase protective sexual behavior, reduce health disparities, and improve access to and the quality of health-care services for homeless youth.